REVIEW OF PRINCIPLES OF QUANTITATIVE RESTRICTIONS ON DISPUTE SETTLEMENT“EU AND US LAWSUIT FOR THE INDONESIAN GOVERNMENT'S NICKEL EXPORT BAN POLICY BY THE WTO DISPUTE SETTLEMENT BODY - Lusi Puspita Sari; Ariawan (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2023)
The Government of Indonesia through Regulation of the Minister of Energy and Mineral Resources Number 11 of 2019 concerning the second Amendment to Regulation of the Minister of Energy and Mineral Resources Number 25 of 2018 concerning Coal Mining and Mineral Exploitation (Permen ESDM 11/2019) decided to stop exporting nickel ore from from 1 January 2020. This regulation is considered to violate the Quantitative Restriction Principle in Article XI of the General Agreement on Tariffs and Trade (GATT) and is being demanded by the European Union against the Dispute Settlement Body of the World Trade Organization (DSB WTO). This article analyzes the scope of Article XI of the GATT and the conformity of the nickel ore export ban regulation with justification in the GATT regulatory framework. This article uses a normative juridical approach, namely legal research conducted through research on library materials and secondary data. This research is descriptive analytical in nature that analyzes related legal instruments, to provide a thorough and systematic understanding of the scope and application of the Quantitative Restriction Principle.This study shows the results that the Interpretation of Article XI: 1 GATT, Indonesia's export ban regulations can be said to be incompatible with the principle of a quantitative restriction ban. Indonesia in implementing a nickel ore export ban has a background to maintain Indonesia's nickel supply which has been depleting. Due to the depletion of Indonesia's nickel supply, the government decided to downstream and industrialize nickel ore. This background is in line with the exception in Article XI:2 (a) which allows export restrictions for a country's essential products. Even so, based on Article XI: 2 (a), this export restriction must be implemented temporarily.